Problems of the Global Civilization: Economic and Environmental Changes - A. A. Tkachenko (Мир новой экономики, 2018)
The article deals with problems of the world civilization, which, in the author’s opinion, are key in the era of transition to a new economy. Special attention is paid to the agriculture of the least developed countries relating to the assessment of environmental progress; in these countries, the increase in labor productivity is impossible without the growth of professional education of rural residents, and the transfer of new agricultural technologies to the uneducated population is ineffective. The contribution of the Asian countries to the world development is considered. They need a radical reduction in the intensity of energy and natural resources use to improve the quality of life of the population. The fate of the 21st century economy of the relates to the ageing and the solution of the problem of qualitative improvement of the social services system for the elderly population. The important problems of the global economy include the issues of labor for care. The possibilities of accounting for unpaid care work in the System of National Accounts and national estimates of the contribution of such labor to the GDP of a few countries are examined. It is concluded that the introduction of automatic indexation of retirement age is unfruitfulness in accordance with the increase in life expectancy and the conclusion about pension savings as the most important source of long-term capital.